Andrographolide antagonizes the cigarette smoke-induced epithelial-mesenchymal transition and pulmonary dysfunction through anti-inflammatory inhibiting HOTAIR. (15th June 2019) - Xia, Haibo; Xue, Junchao; Xu, Hui; Lin, Min; Shi, Ming; Sun, Qian; Xiao, Tian; Dai, Xiangyu; Wu, Lu; Li, Junjie; Xiang, Quanyong; Tang, Huanwen; et al.
Highlights: CS exposure enhances both lung inflammation and airway remodeling. Elevating of IL-6/STAT3 activation and up-regulates lncRNA HOTAIR in lung tissues of CS-exposed mice. LncRNA HOTAIR regulated by STAT3 is involved in CS-induced EMT and airway remodeling. Andrographolide prevents CS-induced lung dysfunction via anti-inflammatory. Abstract: In cells of the lung surface, cigarette smoke (CS) induces inflammatory and epithelial-mesenchymal transition (EMT), effects that are related to pulmonary dysfunction and Chronic obstructive pulmonary disease (COPD). However, the molecular mechanisms involved remain largely unknown, and potential therapeutic approaches are under development. In the present study, with cell culture and animal studies, we showed that CS exposure causes pulmonary dysfunction and airway remodeling with inflammatory cell infiltration. Consistent with these pulmonary lesions, the inflammatory factors interleukin-6 (IL-6) and interleukin-8 (IL-8) were increased in mice exposed to CS for 4 days. Accordingly, downstream signal transducer and activator of transcription 3 (STAT3) was activated, which up-regulated expression of the lncRNA HOTAIR, and enhancer of zeste homolog 2 (EZH2). In addition, CS exposure led to decreased levels of E-cadherin and to increased N-cadherin, vimentin, and α-SMA, indicating that the EMT was induced in mouse lung tissues. These effects, including increases of IL-6 and HOTAIR, were confirmed in human bronchial epithelial (HBE) cells treated with cigarette smoke extract (CSE). Finally, we established that, in HBE cells, andrographolide reversed the CSE-induced EMT via decreasing IL-6 levels and, in an animal model, prevented CS-induced lung inflammation and small airway remodeling, indicating that it has potential clinical application for CS-induced pulmonary dysfunction and COPD.